1974
DOI: 10.1083/jcb.62.2.305
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Rates of Dna Synthesis in Cultured Mammalian Cell Populations

Abstract: In cultures of a murine mastocytoma, endogenous synthesis of thymidine phosphates, as determined by the incorporation of [3H]deoxyuridine into DNA, was reduced within 15 min to less than 3% of control values by the addition of amethopterin (10 µM) in combination with hypoxanthine and glycine. If [3H]thymidine and unlabeled thymidine were added simultaneously with amethopterin, the increase with time of radioactivity in cellular DNA was linear at least between 30 and 90 min, while radioactivity in the acid-solu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1976
1976
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…The DNA synthesis in cells was determined with the radioactive tracer, 3 H-Me-Thy (thymidine). 20 As shown in Figure 5A (a time study), the DNA synthesis without drug (DMSO control) show an increase of 3 H-Me-Thy incorporation with time. However, in the presence of Tig-S (20ug/ml), the DNA synthesis was inhibited.…”
Section: Inhibition Of Dna Synthesis By Tig-s and Tig-rmentioning
confidence: 83%
See 1 more Smart Citation
“…The DNA synthesis in cells was determined with the radioactive tracer, 3 H-Me-Thy (thymidine). 20 As shown in Figure 5A (a time study), the DNA synthesis without drug (DMSO control) show an increase of 3 H-Me-Thy incorporation with time. However, in the presence of Tig-S (20ug/ml), the DNA synthesis was inhibited.…”
Section: Inhibition Of Dna Synthesis By Tig-s and Tig-rmentioning
confidence: 83%
“…Inhibition of DNA synthesis was determined follows the method described by Siegers et al, 20 in which 3 H-Me-Thy (thymidine) was used as tracer. K562 cells, Human chronic MyelogenousLeukemia (CML), are grown in RPMI-1640.…”
Section: Dna Synthesis Determinationmentioning
confidence: 99%
“…Therefore, the cellular synthesis of thymidine was blocked with methotrexate during the labelling period. This procedure ensures that the specific activity of intracellular thymidine triphosphate is equal to the specific activity of thymidine added to the medium and thus constant under all experimental conditions (1,17). Experiments that are not presented here showed that the incorporation of 3H-thymidine was linear with time for at least 4 hours under all conditions used.…”
Section: Regulation Of Cell Growthmentioning
confidence: 99%
“…Cell proliferation rate can reveal important information on perturbation of the cell cycle and is used routinely in a variety of biomedical research areas, including oncology and drug discovery. Current cell proliferation assays quantify proliferation either directly by incorporating a modified nucleotide (BrdU/EdU) to the newly synthesized DNA (at S phase of cell cycle) [1][2][3] or indirectly by measuring parameters such as total ATP/DNA content, [4][5][6] metabolic rate, 7,8 substrate impedance changes, [9][10][11][12] etc. Most of the direct techniques are static end point assays.…”
Section: Introductionmentioning
confidence: 99%